A queer youth's challenges to normativities of time, space, and queerness: pedagogical encounters in a small town Christian youth group. Issue 3 (4th May 2021) - Schey, Ryan
ABSTRACT: Previous scholarship on queer youth in small town and rural educational contexts has primarily documented educators' perspectives and experiences of youth victimization. Drawing from a broader, interview-based teacher inquiry project, I extend this research by considering a queer youth's voice and agency. Using queer theorizations of time and space, I examine the telling case of Sylvia, a queer young woman in a semi-rural, small Midwestern US town. Through her participation in the educational context of an interdenominational Christian youth group, she experienced pedagogical encounters that helped her challenge and reconfigure normative constructions of time, space, and queerness, which facilitated movement toward greater healthiness and happiness, even as she reproduced racial and class normativities through a politics of respectability. Sylvia's experiences suggest the need to attend to heterogeneity and agency in working with queer rural youth and the importance of considering constructions of time, space, and queerness in queer-inclusive curricular texts.